Persea palustris, Swamp Bay - Michael G. Andreu; Melissa H. Friedman; Mary McKenzie; Heather V. Quintana (EDIS, 2010)
FOR 260, a 2-page fact sheet by Michael G. Andreu, Melissa H. Friedman, Mary McKenzie, and Heather V. Quintana, describes this native evergreen found in swamps, wet flatwoods, and on the edges of canals and marshes, whose fruit is a good food source for birds and mammals, and whose leaves are eaten by larvae of the swallowtail butterfly — scientific and common names, description, allergen, and applications. Includes references. Published by the UF School of Forest Resources and Conservation, June 2010.